1859 Ky. Acts 245, An Act to Amend an Act Entitled “An Act to Reduce to One of the Several Acts in Relation to the Town of Harrodsburg,” § 23 - (:unkn) unknown (General Publisher, 1859)
Prohibited “any slave or free person of color, any gun, pistol, bowie knife, slung shot, sword cane, or other weapon used for the purpose of offence or defence.”
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES